INVESTIGATION OF TECHNICAL PARAMETERS OF CHILLS FOR PRODUCTION OF PISTON CASTINGS - M. A. Sadoha (Литьë и металлургия)
Research of technical parameters of chill molds for production of pistons castings is carried out. It is established that the most optimal thickness of covering on a working surface of chill mold is 0,2–0,5 mm.